Mittag–Leffler stability of fractional order nonlinear dynamic systems - Li, Yan; Chen, YangQuan; Podlubny, Igor (Automatica (Oxford), 2009)
In this paper, we propose the definition of Mittag–Leffler stability and introduce the fractional Lyapunov direct method. Fractional comparison principle is introduced and the application of Riemann–Liouville fractional order systems is extended by using Caputo fractional order systems. Two illustrative examples are provided to illustrate the proposed stability notion.